2017
DOI: 10.1037/per0000191
|View full text |Cite
|
Sign up to set email alerts
|

Using online, crowdsourcing platforms for data collection in personality disorder research: The example of Amazon’s Mechanical Turk.

Abstract: The use of crowdsourcing platforms such as Amazon's Mechanical Turk (MTurk) for data collection in the behavioral sciences has increased substantially in the past several years due in large part to (a) the ability to recruit large samples, (b) the inexpensiveness of data collection, (c) the speed of data collection, and (d) evidence that the data collected are, for the most part, of equal or better quality to that collected in undergraduate research pools. In this review, we first evaluate the strengths and po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
137
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 169 publications
(146 citation statements)
references
References 52 publications
(107 reference statements)
7
137
0
2
Order By: Relevance
“…Although they were similar in terms of profiles of values and personality traits, SSSE was predicted positively and communal narcissism was predicted negatively by neuroticism (Rogoza & Fatfouta, ). Thus, the status of vulnerable communal narcissism remains unclear, and future studies are needed as, on the one hand, SSSE represents grandiosity and was located near Gamma‐Plus/Integration, while, on the other hand, it is positively associated with neuroticism, which disentangles vulnerable from grandiose narcissism (Miller, Crowe, Weiss, Maples‐Keller, & Lynam, ).…”
Section: Discussionmentioning
confidence: 99%
“…Although they were similar in terms of profiles of values and personality traits, SSSE was predicted positively and communal narcissism was predicted negatively by neuroticism (Rogoza & Fatfouta, ). Thus, the status of vulnerable communal narcissism remains unclear, and future studies are needed as, on the one hand, SSSE represents grandiosity and was located near Gamma‐Plus/Integration, while, on the other hand, it is positively associated with neuroticism, which disentangles vulnerable from grandiose narcissism (Miller, Crowe, Weiss, Maples‐Keller, & Lynam, ).…”
Section: Discussionmentioning
confidence: 99%
“…First, although samples collected from MTurk tend to be more ethnically diverse than a typical undergraduate research pool population (Buhrmester, Kwang, & Gosling, 2011;Miller, Crowe, Weiss, Maples-Keller, & Lynam, 2017), participants were relatively homogeneous and limited to individuals residing in the United States. As a result of this White American-centric population, we cannot presume that the identified structure will replicate in other countries and cultural contexts.…”
Section: M I Tati On S and F U Ture Di Re Cti On Smentioning
confidence: 99%
“…Our reliance on an online data collection approach is another potential limitation. Although there are a number of advantages to the use of crowdsourcing approaches like MTurk (see Chandler & Shapiro, 2016;Miller et al, , 2017, for reviews), the equivalency of these assessments across in-person administrations and online administrations has not been formally assessed and such equivalency cannot necessarily be assumed (see Bagby, Ayearst, Morariu, Watters, & Taylor, 2014, for a discussion of these issues). Nonetheless, previous examinations have suggested that personality measures tend to show equivalence across these administration modalities (Meade, Michels, & Lautenschlager, 2007).…”
Section: M I Tati On S and F U Ture Di Re Cti On Smentioning
confidence: 99%
“…Despite discussion of potentially far-reaching implications, we advise caution to not overgeneralize these effects to alternative sample frames (e.g., a more representative adult sample; child/adolescent samples; clinical samples). For example, college-student samples tend to be rather psychologically healthy (Miller, Crowe, Weiss, Maples-Keller, & Lynam, 2017), suggesting the present study was operating under a limited range of participant IVC. This possibility implies we may have underestimated the influence of IVC in the present study.…”
Section: Strengths Limitations and Future Directionsmentioning
confidence: 91%